Gazprom - threat to Europe? - Czarny, Elżbieta; Menkes, Jerzy; Toporowski, Patryk (Economics and Business Review, 2009)
The dominant part of production and dispatch of natural gas goes through Gazprom, a company controlled by the state authorities of Russia. We analyze the threats resulting from the strengthening economic and political position of Gazprom. We analyze the most important symptoms of Gazprom's increasing market power (international price discrimination, elimination of competitors, overtaking companies on the related markets) making it a natural monopolist on the Europe an market of natural gas and its dispatch. We analyze Gazprom's ownership structure demonstrating increasing interdependence between the firm and Russia. We discuss potential scenarios of using Gazprom's supplies of gas as a weapon against European countries. (original abstract)